How addressing menstrual health and hygiene may enable progress across the Sustainable Development Goals - Marni Sommer; Belen Torondel; Julie Hennegan; Penelope A. Phillips-Howard; Thérèse Mahon; Albert Motivans; Garazi Zulaika; Caitlin Gruer; Jacquelyn Haver; Bethany A. Caruso; Monitoring Menstrual Health and Hygiene Group (Taylor & Francis Group, 2021)
There is increasing global attention to the importance of menstrual health and hygiene (MHH) for the lives of those who menstruate and gender equality. Yet, the global development community, which focuses on issues ranging from gender to climate change to health, is overdue to draw attention to how addressing MHH may enable progress in attaining the Sustainable Development Goals (SDGs). To address this gap, we undertook a collective exercise to hypothesize the linkages between MHH and the 17 SDGs, and to identify how MHH contributes to priority outcome measures within key sectoral areas of relevance to menstruating girls in low- and middle-income countries. These areas included Education, Gender, Health (Sexual and Reproductive Health; Psychosocial Wellbeing), and Water, Sanitation and Hygiene (WASH). These efforts were undertaken from February - March 2019 by global monitoring experts, together with select representatives from research institutions, non-governmental organizations, and governments (n = 26 measures task force members). Through this paper we highlight the findings of our activities. First, we outline the existing or potential linkages between MHH and all of the SDGs. Second, we report the identified priority outcomes related to MHH for key sectors to monitor. By identifying the potential contribution of MHH towards achieving the SDGs and highlighting the ways in which MHH can be monitored within these goals, we aim to advance recognition of the fundamental role of MHH in the development efforts of countries around the world.